Evaluation of mosques in terms of thermal comfort and energy consumption in a temperate-humid climate - Atmaca, A. B.; Gedik, G. Zorer (ELSEVIER SCIENCE SA, 2019)
Mosques are a type of religious building of where the frequency of use changes daily. Mosques are used at different hours and intervals. Therefore, they should be analyzed differently from residential and office buildings in terms of thermal comfort. Heating, cooling and air conditioning equipment are used in the mosques to provide thermal comfort. Generally, in order to provide thermal comfort, HVAC systems are used, which consume secondary energy sources. The aim of this study is to measure the indoor thermal comfort levels and their compliance with international standards in two mosques that have natural and mechanical ventilation systems, in addition to different heating-cooling systems. In order to monitor the electrical energy consumed during the process of maintaining the thermal comfort in the mosques, annual electrical energy consumption data were obtained via energy analyzers and electric bills. The thermal comfort values were compared to the international standards. By taking into account the results of the measurements and obtained energy data, design proposals for future mosques and recommendations for scheduling air conditioning systems according to building usage practices are presented. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Thermal comfort; Energy; Mosques; Temperate-humid climate; Energy efficiency; BUILDINGS; SYSTEM; OCCUPANCY; IMPACT; Construction & Building Technology; Energy & Fuels; Engineering